Thermodynamic analysis and experimental study of electrode reactions and open circuit voltages for methane-fuelled SOFC. (27th November 2020) - Tu, Baofeng; Wen, Hao; Yin, Yanxia; Zhang, Fujun; Su, Xin; Cui, Daan; Cheng, Mojie
Abstract: Natural gas is one of the most important fuels for solid oxide fuel cell (SOFC). The relationships among the reactions of methane over the nickel-based anode, fuel compositions, carbon deposition, electromotive force (EMF) and open circuit voltage (OCV) of SOFC are investigated in this work. With the increase of temperature, EMF and OCV of SOFC decrease gradually when the cell uses humidified hydrogen as fuel. Reactivity of methane increases gradually with the increase of temperature, which can affect the EMF and OCV of SOFC. When the humidified mixture of nitrogen and methane is used as the fuel, the EMF and OCV of SOFC increase gradually with the increase of temperature. EMF and OCV of SOFC with humidified mixture of hydrogen and methane (MCH4 : MH2 : MH2O  = 12.2: 85.3: 2.5) as fuel decrease gradually with the increase of temperature when the temperature is lower than 873 K, which is similar to that with humidified hydrogen as fuel. While when the temperature is higher than 923 K, the EMF and OCV of SOFC with humidified mixture of hydrogen and methane as fuel increase gradually with the increase of temperature, which is similar to that with humidified mixture of nitrogen and methane as fuel. OCV of SOFC is mainly affected by thermodynamic equilibriums for methane-fuelled SOFC when the anode activity is high enough, which is close to the EMF calculated according to the thermodynamic equilibriums. While with the increase of carbon deposition, the anode activity decreases apparently and the OCV of SOFC also decreases apparently, which shows that the OCV is affected by the anode activity for methane-fuelled SOFC when the anode activity is low. Highlights: OCV of SOFC is mainly affected by thermodynamic equilibrium at high anode activity. For H2 and CH4 mixed fuel, OCV change is similar to that of H2 at low temperature. OCV change for H2 and CH4 mixed fuel is similar to that of CH4 at high temperature. Carbon deposition can lead to the decreases of anode activity and OCV of SOFC. OCV is affected by anode activity for methane-fuelled SOFC at low anode activity.